2022
DOI: 10.1002/essoar.10510483.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DeepLandforms: A Deep Learning Computer Vision toolset applied to a prime use case for mapping planetary skylights

Abstract: The exploration of terrestrial planets in the Solar System was and still is performed mainly on data that cover almost all the electromagnetic spectrum, acquired over the last century by several types of orbiters, rovers, and landers. Planetary data volumes are constantly increasing both in quality and quantity, with the contribution of both public and private entities.Imagery has always been the primary resource for researchers in planetary sciences, especially for geologists and geomorphologists. In the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…A recent study reported the development of a deeplearning program that detects the cave entrance candidate automatically (Nodjoumi et al 2021). The deep learning model learns the patterns of the satellite image of cave entrance candidates and applies the patterns to the new surface regions to detect new cave entrance candidates.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A recent study reported the development of a deeplearning program that detects the cave entrance candidate automatically (Nodjoumi et al 2021). The deep learning model learns the patterns of the satellite image of cave entrance candidates and applies the patterns to the new surface regions to detect new cave entrance candidates.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The original data used for this study are available at publicly data archive NASA PDS Geoscience Node ODE (PDS Geosciences Nodes, 2021). Data sets for this research are available in these in-text data citation references (Nodjoumi, 2021a) with license GPLv2+ and available at: https://doi.org/10.5281/zenodo.7351391. Software for this research is available in these in-text data citation references (Nodjoumi, 2021c): with license GPLv2+ and available at: https://doi.org/10.5281/zenodo.7488867.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Data sets for this research are available in these in-text data citation references (Nodjoumi, 2021a) with license GPLv2+ and available at: https://doi.org/10.5281/zenodo.7351391. Software for this research is available in these in-text data citation references (Nodjoumi, 2021c): with license GPLv2+ and available at: https://doi.org/10.5281/zenodo.7488867. All base images of the figures have been prepared using QGIS software 3.16 LTS and then processed with Affinity Publisher 1.1.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…OR PEER REVIEW 4 of 34 Automatic mapping and classification are a new approach in planetary geology (e.g., [25][26][27][28][29]) and can drastically reduce the effort required for investigations of surface features. Nevertheless, to date, there have been a rather limited number of examples of this approach pertaining to geological investigations of Mars (e.g., [28,[30][31][32][33][34][35]). Machine learning is increasingly used as an application in industry.…”
Section: For Peer Review 2 Of 34mentioning
confidence: 99%